Machine learning-assisted quorum sensing molecules regulate growth progression and bioactivity of an oxygenic photobiofilm for non-aeration greywater purification - Beibei Wu; Libo Xia; Qian Li; Xiaocai Cui; Ting Ran; Yangrui Huang; Yun Zhou (Bioresource Technology, 2026)

Unmeasurable parameter-informed surface settlement prediction model based on CVAE - Gan Wang; Qian Fang; Ran Li; Jianying Wei; Panpan Guo; Yixian Wang (Tunnelling and Underground Space Technology, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

An ultrathin triazine-anchored hypercrosslinked and nonflammable solid polymer electrolyte for safe Li metal batteries - Ran Wang; Yongle Yan; Zelin Lv; Xiaoxiao Li; Xutao Liang; Yang Gao; Mengchao Li; Lifeng Hou; Shi Wang; Zhong Jin; Qian Wang (Chemical Engineering Journal, 2026)

Co-formate framework combined with halogen bond-based deep eutectic solvent for trifluoroacetic acid detection - Ming Jin; Chong Qian; Chen Fan; Jie Li; Ran Duan (Journal of Environmental Chemical Engineering, 2026)

Trace ammonia-assisted binary solvothermal etching for highly stable micron-sized porous silicon/carbon anodes - Fenghui Li; Qian Zhang; Hao Wu; Ping Li; Zhanyong Guo; Ran Zhang; Lianbang Wang (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

Active intermediate water-mediated kinetic promotion for synergistic solar evaporation and photocatalytic mineralization - Xuanting Li; Jinchi Li; Xinrong Huang; Qian Chen; Xinyu Li; Hongbing Wang; Jiang Gong; Ran Niu; Yi Lu; Xiaoke Li (Chemical Engineering Journal, 2026)

The saturation degree of dietary fatty acids alters the phenotypes of lipoprotein subclasses and plasma metabolome in piglets - Ying Li; Yajie Wang; Ran Ma; Zhihua Li; Zemeng Feng; Xiangfeng Kong; Qian Zhou; Xiaoming Guo; Yulong Yin; Yongning Wu; Qinghua He (Food Chemistry, 2026)

Structure-driven RNA remodeling underlies broad substrate recognition by NSUN2 - Qian Hu; Wen Yang; Yunyun Yu; Ran Yi; Yutong Zhang; Leyuan Duan; Fudong Li; Kaiming Zhang; Qingguo Gong; Shanshan Li (Science China Life Sciences, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Variation analysis of natural ventilation and air temperature within a greenhouse cluster using a large-scale 3D CFD modelling - Ran Liu; Pierre-Emmanuel Bournet; José Luis Guzmán; Qian Tingting; Ming Li; Xinting Yang (Computers and Electronics in Agriculture, 2026)

Bacterial, viral and environmental interactions shape antibiotic resistance genes in China's anaerobic-anoxic-oxic wastewater treatment systems - Qian Liu; Jie Chen; Ran Xu; Cong Huang; Nanqi Ren; Shuhong Gao; Wei Li; Xiaodong Xin; Sihao Lv; Siqi Yang; Weiwei Ben; Ai-Jie Wang (Water Research, 2026)

Co-occurrence and reduction mechanisms of microbe-derived dissolved organic nitrogen and nitrous oxide in an oxygenic photobiofilm - Ting Ran; Yu Zhou; Xiaocai Cui; Qian Li; Yangrui Huang; Yun Zhou (Chemical Engineering Journal, 2026)

Hydrogel-based electrochemical microneedles biosensor for sensitive monitoring of lactic acid in interstitial fluid - Yiyue Qu; Ran Chen; Jie Chen; Qian Li; Mostafa R. Abukhadra; Ahmed M. ElSherbeeny; Lili Jin; Qingwei Jiang; Shilun Feng; Shengtai Bian (Analytica Chimica Acta, 2026)

Heat treatment affects gastric digestion kinetics but not amino acid bioavailability of milk proteins: a pig study - Xiyu Qin; Caiziyu Yu; Xiaolu Geng; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Menghui Wang; Xiaomin Ren; Yanling Hao; Ran Wang; Yixuan Li; Pengjie Wang; et al. (Food Chemistry, 2025)

Lipidomic profiling of cutaneous surface lipid alterations in sensitive scalp in Beijing - Ran Li; Qian Jiao; Liya Song; Youjie He; Huaming He; Cheng Zhou; Yan Jia (Chemistry and Physics of Lipids, 2025)

An improved weather routing method based on non-uniform waypoint network - Ran Cao; Longxia Qian; Mei Hong; Dongyu Li; Tianhao Zhu (Ocean Engineering, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Potential role of dietary whole grains in Alzheimer's disease: bioactive components, mechanistic insights, and epidemiological evidence - Meng Shen; Xinru Yu; Suyang Wu; Ju Qiu; Ran Wang; Kai Li; Qian Zhang (Trends in Food Science & Technology, 2025)

Ecological stoichiometry of carbon, nitrogen, phosphorus, and silicon in coastal salt marsh plants and its implications for carbon sink management - Xinyu Zhang; Zhaoliang Song; Yuntao Wu; Lele Wu; Qiang Li; Qian Hao; Shaopan Xia; Yidong Wang; Xiangbin Ran; Yunying Fang; Hailong Wang (Journal of Environmental Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Aging influences protein digestion, absorption and amino acid metabolism - Lili Qiu; Qianqian Huang; Wenhao Li; Qian Zhang; Jun Zhou; Juan Chen; Yixuan Li; Ran Wang; Pengjie Wang; Siyuan Liu; Bing Fang; Xiaoyu Wang (Biogerontology, 2025)

Synergies between corporate social responsibility precedence and sustainable development goals: A pathway to corporate‐led change - Ran Zhang; Qian (Jan) Li (Journal of Industrial Ecology, 2025)
This study examines the intersection of corporate social responsibility (CSR) precedence, circular economy (CE) practices, and the United Nations Sustainable Development Goals (SDGs) through the theoretical frameworks of the organizational culture and dynamic capabilities theory. We explore how historical CSR commitments influence firms’ resource utilization, emissions, waste management, and integration of sustainable practices such as renewable energy consumption and water recycling, using panel regressions with fixed effects and Heckman two‐stage regressions, analyzing data from 1072 public traded US firms from 2007 to 2017. Our findings suggest that firms with a robust history of CSR activities are better positioned to reduce their environmental footprint and enhance their alignment with specific SDG targets, particularly those related to responsible consumption and production (SDG 12) and climate action (SDG 13). Through a comprehensive analysis grounded in organizational culture theory, we demonstrate that firms with a strong CSR precedence foster a green organizational culture, which supports sustainable operational strategies and increases the capability to achieve sustainable outcomes. Drawing on dynamic capability theory, this study underscores the role of CSR precedence in strengthening a firm's capability to adapt and reconfigure resources in response to changing environmental demands, promoting a transition toward a CE, and thereby contributing to the broader objectives of environmental sustainability.

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Current Status and Progress in Stem Cell Therapy for Intracerebral Hemorrhage - Ning Ding; Ran Luo; Qian Zhang; Huanhuan Li; Shuixian Zhang; Huanran Chen; Rong Hu (Translational Stroke Research, 2025)

Multi-objective optimization design of an umbilical cross-sectional layout based on the sequential least squares quadratic programming algorithm - Qian Ran; Meng Li; Fusen Peng; Yanlian Du; Yijun Shen; Yongqi Ma (Ocean Engineering, 2025)

Machine learning-based prediction of non-aeration linear alkylbenzene sulfonate mineralization in an oxygenic microalgal-bacteria biofilm - Libo Xia; Beibei Wu; Xiaocai Cui; Ting Ran; Qian Li; Yun Zhou (Bioresource Technology, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

A green and effective glucoside surfactant assisted micellar electrokinetic chromatography for the separation of phenolic compounds from medicinal plant using response surface methodology - Qian-Xue Shen; Yan-Hua Jiao; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Heterogeneous marine environments diversify microbial-driven polymetallic nodule formation in the South China Sea - Mingyan Lai; Qian Liu; Xiaogu Wang; Dong Sun; Lihua Ran; Xiaohu Li; Chenghao Yang; Bo Lu; Xue-Wei Xu; Chun-Sheng Wang (Frontiers in Marine Science, 2024)
Most studies on the genesis of polymetallic nodules suggested that nodules in the South China Sea (SCS) are hydrogenetic; however, the complexity and the heterogeneity in hydrology and geochemistry of the SCS might cause different processes of nodule formation, impacting their application and economic value. Microbial-mediated ferromanganese deposition is an important process in nodule formation, but the related microbial potentials are still unclear in the SCS. In this study, we sampled in three typical regions (A, B, and C) of the SCS enriched with polymetallic nodules. Firstly, we investigated environmental and microbial characteristics of the water columns to determine the heterogeneity of upper seawater that directly influenced deep-sea environments. Then, microbial compositions and structures in sediment cores, overlying waters, and nodules (inside and outside) collected within the same region were analyzed for inferring features of nodule environments. Microbial interactions between nodules and surrounding environments were estimated with collinear network analysis. The microbial evidence indicated that geochemical characteristics in deep sea of the SCS that were key to the polymetallic nodule formation were severely affected by organic matter flux from upper water column. The sediment in region A was sub-oxic due to the large input of terrigenous and phytoplankton-derived organic matter, potentially enhancing the overflow of reduced metals from the porewater. The intense microbial interaction between nodules and surface sediment reinforced the origin of metals for the ferromanganese deposition from the sediment (diagenetic type). Contrarily, the sediments in regions B and C were relatively rich in oxygen, and metal ions could be majorly supplied from seawater (hydrogenetic type). The large discrepancy in microbial communities between nodule inside and remaining samples suggested that nodules experienced a long-term formation process, consistent with the feature of hydrogenetic nodules. Overall, distributions and interactions of microbial communities in nodules and surrounding environments significantly contributed to the nodule formation in the SCS by manipulating biogeochemical processes that eventually determined the source and the fate of metal ions.

Strategies, techniques and applications for food authentication based on carbohydrates: A review - Li-feng Li; Xi Shi; Si-min Qi; Xue-ting Zhang; Hau-Yee Fung; Qian-ran Li; Quan-bin Han (Carbohydrate Polymers, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Overcoming polarization and dissolution of manganese-based electrodes to enhance stability in electrochemical lithium extraction - Yingjun Qiao; Yonggan Ran; Zhiqiang Qian; Bing Zhao; Chengpeng Li; Zhong Liu (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Fe/Co bimetallic nanozyme disrupting tumorous Self-Regulatory pathways to potentiate ferroptosis - Qing Liu; Qian Chen; Xi Deng; Yutong Zhu; Zhangpeng Shi; Runjie Miao; Ming Ma; Nian Ran; Cheng Li; Hangrong Chen (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

Enhanced interfacial effect via acid theory with boosted photocatalytic performance of nitenpyram removal - Ran Chen; Bo Xu; Heping Cheng; Qianqian Fang; Minghai Ma; Liping Qian; Shunli Wan; Shengyou Xu; Yan Li; Lei Zhang; Shikai Xiang (Chemosphere, 2024)

Dynamic risk evaluation of supersaturated dissolved gas at a confluence with unsteady flow conditions - Zhuo Chen; Jingjie Feng; Ran Li; Qian Ma; Ruifeng Liang; Jingying Lu; Jingyang Xue (Journal of Hydrology, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

A repertoire of single nucleotide polymorphisms (SNPs) of major fecundity BMPR1B gene among 75 sheep breeds worldwide - Chunna Cao; Qian Zhou; Yuxin Kang; Zhanerke Akhatayeva; Peiyao Liu; Yuheng Bai; Ran Li; Yu Jiang; Qingfeng Zhang; Xianyong Lan; Chuanying Pan (Theriogenology, 2024)

Enhancing predictions of remedial reagent transport via a vertical groundwater circulation well with high-resolution aquifer characterization - Zaiyong Zhang; Jingbo Yang; Chengcheng Gong; Wenke Wang; Bin Ran; Guangqi Wang; Qian Zhang; Yu-Li Wang (Science of The Total Environment, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Conversion mechanism for solving the end-stop problem of hydraulic power take-off system for wave energy - Dahai Zhang; Chenglong Li; Ran Bi; Xin Huang; Zhiwei Sun; Tianlong Lan; Yuankui Wang; Ting Huang; Peng Qian (Ocean Engineering, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

The throttling characteristics of supercritical carbon dioxide in the flowback process of CO2 fracturing - Mingzheng Qiao; Zefeng Jing; Ran Zhou; Cheng Chen; Xupeng Zou; Yong Li; Qian Zou (Gas Science and Engineering, 2024)

Di(2-ethylhexyl) phthalate induces reproductive toxicity and transgenerational reproductive aging in Caenorhabditis elegans - Ying Zhang; Jingjing Li; Wei Shi; Lu Lu; Qian Zhou; Hu Zhang; Ran Liu; Yuepu Pu; Lihong Yin (Environmental Pollution, 2023)

Biofilm bioactivity affects nitrogen metabolism in a push-flow microalgae-bacteria biofilm reactor during aeration-free greywater treatment - Beibei Wu; Ting Ran; Sibei Liu; Qian Li; Xiaocai Cui; Yun Zhou (Water Research, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Phenotype-genotype mapping reveals the betaine-triggered L-arginine overproduction mechanism in Escherichia coli - Shuai Jiang; Heyun Wu; Zhuoyue Yao; Ran Li; Qian Ma; Xixian Xie (Bioresource Technology, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Alkyl halide formation from degradation of carboxylic acids in the presence of Fe(III) and halides under light irradiation - Xueling Bai; Qian Yang; Yang Guo; Baoqiang Hao; Renyuan Zhang; Ran Duan; Jing Li (Water Research, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Numerical modelling and field monitoring study on large-span tunnelling using pretensioned bolt–cable combined support system - Jiwei Luo; Dingli Zhang; Zhenyu Sun; Qian Fang; Daoping Liu; Tong Xu; Ran Li (Tunnelling and Underground Space Technology, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Specific PhytOC fractions in rice straw and consequent implications for potential of phytolith carbon sequestration in global paddy fields - Xiaomin Yang; Zhaoliang Song; Laodong Guo; Jingxu Wang; Yilun Ni; Zimin Li; Qian Hao; Qiang Li; Lele Wu; Wei Kuang; Yang Liu; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

The driving factors and buffering mechanism regulating cropland soil acidification across the Sichuan Basin of China - Aiwen Li; Chengji Li; Yuanyuan Zhang; Qian Deng; Hongyan Fang; Bin Zhao; Min Ran; Liangying Song; Jingling Xue; Qi Tao; Rong Huang; Yiding Li; et al. (CATENA, 2023)

Associations of exposure to multiple metals with the risk of age-related cataract in Anhui, China: a case–control study - Yan-Qing Li; Qian Wang; Ran Liu; Guo-Ao Li; Jia-Liu He; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Mechanisms underlying microRNA-222-3p modulation of methamphetamine-induced conditioned place preference in the nucleus accumbens in mice - Qing Shang; Jing Wang; Zhijia Xi; Baoyao Gao; Hongyan Qian; Ran An; Gaojie Shao; Hua Liu; Tao Li; Xinshe Liu (Psychopharmacology, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Two new chemical constituents from the rhizomes of Actaea dahurica - Sen-Ju Ma; Hai-Bo Li; Jun-Ran Shao; Qian-Qian Pang; Ting Li; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Dysregulation within the salience network and default mode network in hyperthyroid patients: a follow-up resting-state functional MRI study - Bo Liu; Li Wen; Qian Ran; Si Zhang; Junhao Hu; Mingfu Gong; Dong Zhang (Brain Imaging and Behavior, 2020)

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Cumulative effects of cascade hydropower stations on total dissolved gas supersaturation - Qian Ma; Ran Li; Jingjie Feng; Jingying Lu; Qin Zhou (Environmental Science and Pollution Research, 2018)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

Prediction of brittleness based on anisotropic rock physics model for kerogen-rich shale - Ke-Ran Qian; Zhi-Liang He; Ye-Quan Chen; Xi-Wu Liu; Xiang-Yang Li (Applied Geophysics, 2017)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

A review of inexact optimization modeling and its application to integrated water resources management - Ran Wang; Yin Li; Qian Tan (Frontiers of Earth Science, 2015)

Cloning and in silico analysis of a cinnamyl alcohol dehydrogenase gene in Pennisetum purpureum - RAN TANG; XIANG-QIAN ZHANG; YOU-HAN LI; XIN-MING XIE (Journal of Genetics, 2014)

Combined Effect of Copper and Cadmium on Heavy Metal Ion Bioaccumulation and Antioxidant Enzymes Induction in Chlorella vulgaris - Haifeng Qian; Jingjing Li; Xiangjie Pan; Liwei Sun; Tao Lu; Hongyu Ran; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2011)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)